2011
DOI: 10.3758/s13414-011-0226-3
|View full text |Cite
|
Sign up to set email alerts
|

Longer is not better: nonconscious overstimulation reverses priming influences under interocular suppression

Abstract: Previous research has shown that stimuli rendered invisible through masking can be sufficiently processed to induce nonconscious influences and facilitate subsequent recognition. However, masking paradigms are methodologically restricted such that stimuli cannot be presented for longer than a few tens of milliseconds, potentially restricting the strength of nonconscious influences. By adapting a masked face repetition priming paradigm to a recent interocular suppression method, we investigated whether longer p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 53 publications
4
46
1
Order By: Relevance
“…We validated this hypothesis by running a control experiment, in which a visible adaptor presented during 7 s at 0.08 Michelson contrast (i.e., with higher perceptual strength) exerted not an attractive, but a repulsive effect (effect = À0.74, t(5) = À2.81, p = 0.038). This result is similar to previous studies documenting the relationship between visual adaptation and perceptual strength of orientation features (Faivre & Kouider, 2011b), faces (Barbot & Kouider, 2012), or translational motion (Kanai & Verstraten, 2005).…”
Section: Biological Motionsupporting
confidence: 81%
See 1 more Smart Citation
“…We validated this hypothesis by running a control experiment, in which a visible adaptor presented during 7 s at 0.08 Michelson contrast (i.e., with higher perceptual strength) exerted not an attractive, but a repulsive effect (effect = À0.74, t(5) = À2.81, p = 0.038). This result is similar to previous studies documenting the relationship between visual adaptation and perceptual strength of orientation features (Faivre & Kouider, 2011b), faces (Barbot & Kouider, 2012), or translational motion (Kanai & Verstraten, 2005).…”
Section: Biological Motionsupporting
confidence: 81%
“…We found that long-lasting apparent motion adaptors induced repulsive effects (i.e., perceiving the probe as moving horizontally after a vertical adaptor, and vice versa), while biological motion adaptors induced attractive effects (i.e., perceiving the probe as a female after a female adaptor, and vice versa). Along this line, it has been shown that increasing the duration of invisible stimuli could reverse attractive into repulsive effects (Barbot & Kouider, 2012;Faivre & Kouider, 2011b;Kanai & Verstraten, 2005). Beyond stimulus duration, the temporal dynamics that defined apparent and biological motion likewise differed: while the temporal structures carrying the direction of apparent motion ranged from 100 ms to 1200 ms (i.e., different ISIs between disks), those carrying the gender of point-light walkers ranged from 1 s (i.e., one walk cycle in the fast kinematic condition) to 3 s (i.e., one walk cycle in the slow kinematic condition).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that not only dorsal, but also ventral visual areas may exhibit preserved unconscious processing under CFS (Sterzer et al, 2008). Furthermore, behavioral evidence indicates that unconscious priming extends to images that are assumed to be processed along the ventral stream (Barbot and Kouider, 2012). For those reasons, the apparent dissociation between dorsal and ventral visual brain regions brought about by CFS does not seem to hold, and it can therefore be questioned whether the study by Sakuraba et al (2012) successfully isolated dorsal stream processes.…”
Section: Review Of Sakuraba Et Almentioning
confidence: 85%
“…Follow-up studies suggested that the priming effects were in fact based on elongated shape and not on tool category [ (Sakuraba, Sakai, Yamanaka, Yokosawa, & Hirayama, 2012), also see (Hebart & Hesselmann, 2012)], a finding which seems harder to reconcile with the notion of preserved action-relevant representations in parietal cortex under CFS. Note that prime durations were considerably longer (1000-3000 ms) in the numerical priming experiments by Bahrami et al (2010) than in most previously mentioned category priming experiments ($200 ms), which might have negatively influenced the numerical priming effects under interocular suppression (Barbot & Kouider, 2012).…”
Section: Privileged Access Of Visual Information To Dorsal Stream Promentioning
confidence: 98%